Experimental Investigation on Temperature Effects of Cryogenic Pressure-Sensitive Paint - Peng Qiao; Jifei Wu; Hui Huang; Guoshuai Li; Da Li; Hai Du (Aerospace)
Pressure-sensitive paint (PSP) is an important wind tunnel testing technology. Compared with conventional PSP, the performance and test accuracy of cryogenic PSP are still immature. Therefore, investigating how to improve the pressure sensitivity of cryogenic PSP and reduce the interference of temperature effect is of great significance. By studying the PSP luminescence characteristics at different time points, temperatures, and pressures, some interesting phenomena have been discovered. When the temperature reaches 323 K, PSP can accelerate aging, leading to significant and irreversible changes in coating performance. Additionally, the effect of temperature on the luminescence characteristics of PSP shows significant differences over time. This unusual phenomenon may be related to the microstructure change in PTMSP (PtTFPP) coatings over time. In the beginning, PTMSP coating has high activity and spacing between PtTFPP luminescence centers, which change significantly with the microstructure as the temperature decreases. This might result in a stronger concentration quenching of PtTFPP, which counteracts the expected enhancement of luminescence efficiency typically caused by the temperature decrease. After 72 h, the microstructure of the coating tends to be stable, and the effect of temperature on the fluorescence characteristics of PSP becomes a thermal quenching law similar to that of traditional PSP. This discovery can provide a more precise basis for correcting the temperature effect for cryogenic PSP coatings with varying service lives.